EFFECTIVENESS OF ANTI-BULLYING SCHOOL PROGRAM: PERCEPTION SURVEY OF GRADE XII STUDENTS AT SMAS AL AZHAR MEDAN - Raudhah Carolina Herera Nasution; M. Daffa Al-Azka Harahap; Qeisya Hafizhah Malvira; Kerisna Chairsyah Abdillah Harahap; Rizky Ramadhan (CV. RADJA PUBLIKA, 2024)
This study aims to analyze the effectiveness of the anti-bullying school program at SMAS Al Azhar Medan based on the perceptions of grade XII students. The program includes various initiatives such as positive discipline, Roots Indonesia, anti-bullying day, and buddy program. The method used was a survey involving 144 respondents from grade XII students. The results showed that most students (55.6%) felt that the program was effective in creating a safe and comfortable environment. As many as 33.3% of students felt comfortable interacting, while 11.1% of students considered the program ineffective. The t-test and ANOVA showed significant differences in student perceptions based on various factors. Based on these findings, it can be concluded that although the anti-bullying program at SMAS Al Azhar Medan has a positive impact, evaluation and improvement are still needed to increase its effectiveness. This study provides recommendations for further development of programs that can strengthen awareness and prevention of bullying in schools.